Conceptualising Images of God: Distinguishing Between God of Grace and God of Law - Holdsworth, John (Rural theology, 2024)
Clearly differentiated images of God are essential tools for empirical theologians and other data-based academics researching within the field of psychology. However, images so far suggested do not correspond to those used by biblical scholars. The latter tend to regard differentiated images of God as alien to the style and understanding of the Bible. However, at two creative points within the biblical tradition itself, the post-Exile and post-Easter theologians developed sharply defined understandings of God, and hence the religious life and message. These could be described as “law” and “grace” approaches, using biblical language; but the basic idea has to do with a question set early in Genesis about the comparative success of God’s grace as opposed to human sin, generating a division between optimism and pessimism, and responses ranging from “confident” to “anxious”. These categories may be worth exploring further for their usefulness in empirical study.